Resveratrol Modulates the Gut Microbiota and Inflammation to Protect Against Diabetic Nephropathy in Mice - Cai, Ting-Ting; Ye, Xiao-Long; Li, Ru-Run; Chen, Hui; Wang, Ya-Yun; Yong, Hui-Juan; Pan, Ming-Lin; Lu, Wei; Tang, Ying; Miao, Heng; Snijders, Antoine M.; Mao, Jian-Hua; et al. (Frontiers in Pharmacology, 2020)
Oral administration of resveratrol is able to ameliorate the progression of diabetic nephropathy (DN); however, its mechanisms of action remain unclear. Recent evidence suggested that the gut microbiota is involved in the metabolism therapeutics. In the current study, we sought to determine whether the anti-DN effects of resveratrol are mediated through modulation of the gut microbiota using the genetic db/db mouse model of DN. We demonstrate that resveratrol treatment of db/db mice relieves a series of clinical indicators of DN. We then show that resveratrol improves intestinal barrier function and ameliorates intestinal permeability and inflammation. The composition of the gut microbiome was significantly altered in db/db mice compared to control db/m mice. Dysbiosis in db/db mice characterized by low abundance levels of Bacteroides, Alistipes, Rikenella, Odoribacter, Parabacteroides, and Alloprevotella genera were reversed by resveratrol treatment, suggesting a potential role for the microbiome in DN progression. Furthermore, fecal microbiota transplantation, derived from healthy resveratrol-treated db/m mice, was sufficient to antagonize the renal dysfunction, rebalance the gut microbiome and improve intestinal permeability and inflammation in recipient db/db mice. These results indicate that resveratrol-mediated changes in the gut microbiome may play an important role in the mechanism of action of resveratrol, which provides supporting evidence for the gut–kidney axis in DN.